2004
DOI: 10.1158/0008-5472.can-03-3443
|View full text |Cite
|
Sign up to set email alerts
|

GW112, A Novel Antiapoptotic Protein That Promotes Tumor Growth

Abstract: GW112 is a novel gene that has little homology to other known genes. It is overexpressed in a number of human tumor types, especially in those of the digestive system. We show here that GW112 is associated with GRIM-19, a protein known to be involved in regulating cellular apoptosis. Functionally, GW112 could significantly attenuate the ability of GRIM19 to mediate retinoic acid-IFN-␤-mediated cellular apoptosis and apoptosis-related gene expression. In addition, GW112 demonstrated strong antiapoptotic effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
161
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(170 citation statements)
references
References 50 publications
5
161
3
Order By: Relevance
“…It has been reported that olfactomedin 4 interacts with GRIM-19 to attenuate retinoic acid and interferon beta-mediated cellular apoptosis and transient expression of olfactomedin 4 promotes tumor growth in C57/BL/6 mice. 9 Therefore, overexpression of olfactomedin 4 may contribute to carcinogenesis by resistance to apoptosis at least in early stage GC. In contrast, in CRC, it has been reported that olfactomedin 4 down-regulation is found in late stage cases, and in patients with shorter survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that olfactomedin 4 interacts with GRIM-19 to attenuate retinoic acid and interferon beta-mediated cellular apoptosis and transient expression of olfactomedin 4 promotes tumor growth in C57/BL/6 mice. 9 Therefore, overexpression of olfactomedin 4 may contribute to carcinogenesis by resistance to apoptosis at least in early stage GC. In contrast, in CRC, it has been reported that olfactomedin 4 down-regulation is found in late stage cases, and in patients with shorter survival.…”
Section: Discussionmentioning
confidence: 99%
“…8 Although OLFM4 is predominantly expressed in bone marrow, small intestine, colon and prostate, 8 the levels of expression are much lower in normal tissues than in GC tissues. 5 Enhanced olfactomedin 4 expression has been reported in GC by Northern blot analysis 9 and by immunostaining. 10 Because olfactomedin 4 is a secreted N-linked glycoprotein, olfactomedin 4 may serve as a specific serum biomarker for GC; however, the concentration of olfactomedin 4 in serum has not been investigated.…”
mentioning
confidence: 97%
“…We show that APin protein (APIN), taxol resistance-associated gene 3 (TRAG3), cytochrome P450, family 2, subfamily W, polypeptide 1 (CYP2W1), melanoma inhibitory activity (MIA), matrix metalloproteinase-10 (MMP-10), dickkopf homolog 4 (DKK4), GW112, regenerating islet-derived family, member 4 (REGIV), and HORMA domain-containing 1 (HORMAD1) were much more highly expressed in GC than in normal tissues. Among these genes, overexpression of REGIV and GW112 in GC has been reported (Oue et al, , 2005Zhang et al, 2004). Immunohistochemical analysis of MIA, MMP-10, and DKK4 in 151 GC samples revealed that MIA and MMP-10 are frequently overexpressed in GC.…”
Section: Introductionmentioning
confidence: 99%
“…For example, OLFM4 was found to interact with and inhibit the apoptosis promoting factor GRIM-19 [41]. Alternatively, secreted OLFM3 may interact with cell surface receptors or secreted proteins to prevent anoikis signalling.…”
Section: Discussionmentioning
confidence: 99%